Hindu Rituals at the Margins: Innovations, Transformations, Reconsiderations, edited by Linda Penkower and Tracy Pintchman - Ramey, Steven (Religions of South Asia, 2017)
Hindu Rituals at the Margins: Innovations, Transformations, Reconsiderations, edited by Linda Penkower and Tracy Pintchman. Columbia, SC: University of South Carolina, 2014. xiv + 235 pp., $49.95 (hb). ISBN 1-61117-389-5 (hb).